Apsidal motion in massive close binary systems - I: HD 165052, an extreme case? - Ferrero Sosa, Gabriel Antonio (2013)
We present a new set of radial velocity measurements of the spectroscopic binary HD 165052 obtained by disentangling high-resolution optical spectra. The longitude of the periastron (ω = 60 ± 2°) shows a variation with respect to previous studies. We have determined the apsidal motion rate of the system, ω = 12.1 ± 0.° 3 yr-1, which was used to calculate the absolute masses of the binary components: M1 = 22.5 ± 1.0Mȯ and M2 = 20.5 ± 0.9Mȯ. Analysing the separated spectra, we have reclassified the components as O7Vz and O7.5Vz stars.